2013
DOI: 10.1007/s10195-013-0239-x
|View full text |Cite
|
Sign up to set email alerts
|

Divergent elbow dislocation with radial shaft fracture, distal ulnar deformation, and distal radioulnar joint instability: an unclassifiable Monteggia variant

Abstract: Originally described by Monteggia and later classified by Bado, elbow dislocations with concurrent radial and ulnar shaft fractures with distal radioulnar joint (DRUJ) disruption are considered operative cases with high-energy injurious etiologies. Here, we present an unclassifiable Monteggia variant fracture suffered through a high axial load mechanism in a 47-year-old female. The fracture pattern initially exhibited included a divergent elbow dislocation, a radial shaft fracture, plastic deformation of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Each type in our study was demonstrated in previous literature [2][3][4][5][6]. These concomitant fracture-dislocations of the forearms further complicated the DDE in adults, which brought a considerable challenge to orthopaedic surgeons.…”
Section: Discussionsupporting
confidence: 58%
“…Each type in our study was demonstrated in previous literature [2][3][4][5][6]. These concomitant fracture-dislocations of the forearms further complicated the DDE in adults, which brought a considerable challenge to orthopaedic surgeons.…”
Section: Discussionsupporting
confidence: 58%
“…Injuries to the annular ligament and medial collateral ligament were common soft-tissue complications. Although several cases were treated with closed reduction, 10 cases required open surgery to treat fractures or dislocation [9][10][11][12]16,25,27,31,33,34 . Annular ligament, capsule, and bone fragment from the fracture site were commonly listed as reduction-inhibitory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, one case report most closely resembled the variant discussed in our paper. Laratta et al described a posterior ulno-humeral dislocation with anterior radial head dislocation, with an associated radial shaft fracture, as well as disruption of the DRUJ [17] . Ultimately, after a thorough review of the literature, our cases unique pattern of a posterior ulno-humeral and radio-capitellar joint dislocation, and radial shaft fracture without any fracture or deformation to the ulna has not been discussed before to our knowledge.…”
Section: Discussionmentioning
confidence: 99%